2017
DOI: 10.1590/s0102-865020170120000007
|View full text |Cite
|
Sign up to set email alerts
|

A prototype single-port device for pressurized intraperitoneal aerosol chemotherapy. Technical feasibility and local drug distribution

Abstract: A prototype single-port device for pressurized intraperitoneal aerosol chemotherapy. Technical feasibility and local drug distribution 1 AbstractPurpose: To evaluate the technical feasibility and homogeneity of drug distribution of pressurized intraperitoneal aerosol chemotherapy (PIPAC) based on a novel process of intraperitoneal drug application (multidirectional aerosolization). Methods:This was an in vivo experimental study in pigs. A single-port device was manufactured at the smallest diameter possible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Overall, the search identified: 23 stage 0 studies; 18 stage 1 studies and two protocol papers for stage 1 studies; 25 stage 2a studies, one protocol paper and five trial registrations (NCT01854255, NCT02735928, NCT03246321, NCT02604784 and NCT03124394) for stage 2a studies; six stage 2b studies and three protocol papers for stage 2b studies; and three protocol papers for stage 3 studies. Fig .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the search identified: 23 stage 0 studies; 18 stage 1 studies and two protocol papers for stage 1 studies; 25 stage 2a studies, one protocol paper and five trial registrations (NCT01854255, NCT02735928, NCT03246321, NCT02604784 and NCT03124394) for stage 2a studies; six stage 2b studies and three protocol papers for stage 2b studies; and three protocol papers for stage 3 studies. Fig .…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the aerosol has shown that the droplet size is heterogeneous. One group has developed and brought to market a second device to enable PIPAC, but there is currently little information on the technical performance of this device, nor on its use outside Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the latest published studies, it is known today that aerosol-creation and application into the peritoneal cavity is neither biologically nor technically restricted to the MIP ® (18,22,25). The creation of new aerosol-producing devices is becoming increasingly popular in contemporary research (18,26). With regards to untrained personnel, high costs and uncertainty in the handling of PIPAC with MIP ® , this study aimed to investigate a new option to apply PIPAC using of a well-known FDA-approved MC which has been utilized in gastroenterology and pulmonary medicine for years.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, concerns of having no hands-on and clinical experience in handling the technology and potential difficulties might intimidate surgeons from applying PIPAC. Therefore, alternative aerosol-generating devices are developed and examined to meet these concerns (18,25,26). Current difficulties with these new and recently published prototype devices include that these are even less investigated than the original (MIP ® ).…”
mentioning
confidence: 99%
“…Parallel to the population studies, research is progressing in order to improve the procedures, as seen in publications by Khosrawipour et al, [17] and Seitenfus et al, [21][22][23].…”
Section: Introduction and Review Of The Literaturementioning
confidence: 99%